2008
DOI: 10.1002/hlca.200890037
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of β‐Blockers via Hydrolytic Kinetic Resolution of Terminal Oxiranes by Using Bimetallic Chiral {{2,2′‐[Cyclohexane‐1,2‐diylbis(nitrilomethylidyne)]bis[phenolato]}(2−)}cobalt ([Co(salen)])‐Type Complexes

Abstract: The synthesis of chirally pure b-blockers was successfully achieved via hydrolytic kinetic resolution of butyl (AE)-4-(oxiran-2-ylmethoxy)benzeneacetate ((AE)-1) and (AE)-4-(oxiran-2-ylmethoxy)benzeneacetonitrile ((AE)-2) in the presence of bimetallic chiral [Co(salen)]-type complexes. The newly synthesized bimetallic chiral [Co(salen)]-type complexes exhibited excellent enantioselectivities of up to > 98% ee in good yields (Tables 1 -3).Introduction. -The synthesis of chirally pure b-blockers is a very import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The [Co II (salen)] complex A exhibited O 1s core level peak at a binding energy of ca 531 eV, while the transition-metal-containing cobalt-salen-type complexes showed a binding energy at higher value of ca 532 eV, and are in accordance with the earlier literature. [19] The observed change in binding energy of 1 eV (i.e. from ca 531 to 532 eV) for the Co(salen) containing transition-metal sample could be attributed to the differences in the coordination environments of transition metal and confirms the interaction with oxygen of cobalt salen.…”
Section: Tbmementioning
confidence: 94%
See 2 more Smart Citations
“…The [Co II (salen)] complex A exhibited O 1s core level peak at a binding energy of ca 531 eV, while the transition-metal-containing cobalt-salen-type complexes showed a binding energy at higher value of ca 532 eV, and are in accordance with the earlier literature. [19] The observed change in binding energy of 1 eV (i.e. from ca 531 to 532 eV) for the Co(salen) containing transition-metal sample could be attributed to the differences in the coordination environments of transition metal and confirms the interaction with oxygen of cobalt salen.…”
Section: Tbmementioning
confidence: 94%
“…[20] The PKR displays more attractive features with regards to the substrates of HKR. [19] In addition, the nucleophilic components can be varied, and phenols with a wide range of electronic properties are effective substrates. This raises the interesting possibility of applying this methodology to enantioselective catalytic synthesis of β-blockers through PKR.…”
Section: Tbmementioning
confidence: 99%
See 1 more Smart Citation
“…In the previous our study, the dimeric or dinuclear salen complexes have shown the excellent activity in the asymmetric kinetic resolution (AKR) of terminal epoxides. 9 Recently we have isolated the new salen catalysts containing transition metals salts, such as CoCl 2 , Co(NO3)2, FeCl2, NiCl2, in the ligand structure. 10,11 Their catalytic activity and enantioselectivity were dependent on the type of metal salts combined to the salen complexes in AKR reactions.…”
Section: Introductionmentioning
confidence: 99%